The Impact Of Equity Research And Stock Split On Stock Liquidity And Stock Return A Study Case On Indonesia Stock Exchange - Florida, Vera; Soekarno, Subiakto (The Indonesian Journal of Business Administration, 2014)
Abstract- This research is intended to find wether equity research and stock split may create stock liquidity in Indonesia Stock Exchange, effectively. Stock liquidity is measured with liquidity ratio. Hypothesis testing is needed to prove that there are significant increase in stock liquidity after stock split or equity research conducted as well as to determine what kind of listed companies should be permitted to conduct stock split.  The results are equity research increased stock liquidity significantly, stock split increased liquidity at announcement date but it is non significant and liquidity of listed companies with higher stock prices increased significantly when they conducted stock split.   Key word: equity research, stock split, stock liquidity